Uncertainty modelling of service life and environmental performance to reduce risk in building design decisions - Silvestre, José Dinis; Silva, Ana; Brito, Jorge de (Journal of Civil Engineering and Management, 2015)
Life-cycle assessment (LCA) is increasingly used to quantify the environmental impacts of construction materials. However, the relationship between the durability and LCA of these complex products with long life-cycles must be analysed in detail, namely using stochastic data from service life prediction (SLP) studies. However, SLP uncertainty is not yet considered in LCA, thus resulting in insufficiently sound decisions at the design stage. This paper presents the modelling of the uncertainty of SLP using advanced statistical methods and its application in the estimation of SL and corresponding number of replacements of claddings (renderings and stone claddings). These results are used in an interdisciplinary study of SLP and LCA to apply in the stochastic comparison of the LCA of claddings. This methodology aids in the choice of the option with better environmental performance right at the design stage, via the comparison of their standard, deterministic and stochastic LCA results.